Characteristics of occlusion in primary dentition of preschool children of Udaipur, India - Hegde, Sapna; Panwar, Sunil; Bolar, Dinesh Rao; Sanghavi, Mitesh Bharat (European Journal of Dentistry, 2012)
Objective: The present study aimed to study the occlusion characteristics of the primary dentition in a group of 3-5 year-old Indian children and the differences with age in the same group.Methods: The study was a cross-sectional survey based on examination of the primary dentition of 200 preschool children aged 3-5 years who were selected from nursery schools in Udaipur, India, using a stratified random sampling technique. The study group was assessed for the several occlusal parameters, which included primary molar and canine relationship, degree of overjet and overbite, anterior and posterior crossbite, and the presence or absence of physiologic spaces and crowding.Results: Flush terminal plane was more common at 3-4 years of age, mesial step at 4-5 years, and class I canine relationship in both age groups. The prevalence of overjet less than 1 mm and overjet exceeding 1 mm was almost comparable in both groups. Overbite with less than 30% overlap was most frequently observed in both age groups, with 30-60% overlap following closely behind. Physiologic and primate spacing were observed in less than half of the children examined, while a small percentage displayed the presence of either single-segment or two-segment crowding.Conclusion: The present study provided insight into the state of dentition, occlusal pattern, spacing, and crowding in the primary dentition of Indian children of Udaipur. (Eur J Dent 2012;6:51-55)
Keywords: Primary occlusion; occlusion; occlusion characteristics; primary dentition